Influence of spirituality on the conduct of couples during pregnancy under the view of nursing: literature review (Research, Society and Development, 2020)
The objective is to describe the experiences related to the spirituality of pregnant women and their sexual partners from the perspective of nursing. An integrative literature review with a primary search for articles published between 2000 and 2019 is outlined. In the results, eleven articles were selected, of which 55% were obtained from the Web of Science (WOS) database, all written in English, 27% were from 2019, 64% from the Asian continent, 64% from obstetrics and 55% from high-risk pregnant women. Islam represented 45% of the religions found, with Iran and the United States accounting for 27% of the studies. A main category was obtained: "Influence of spirituality on couples behavior during pregnancy" and twelve subcategories. The couple's positive attitudes related to spirituality were perceived. Many women mentioned the trust and divine support for childbirth and birth, it was also found that they were concerned about the fetus and made waivers so that they would be well. In many articles, men were helpful and attentive to the pregnant woman and the baby and wanted to be informed about their health. In all the studies, men were protective and hardworking, several had positive attitudes or feelings related to spirituality. The nurse was identified as a professional who supports and provides information to patients, however, he was not seen as a provider of spiritual support for the pregnant couple. In conclusion, the importance of developing new research on the spirituality of pregnant women and their partners for nursing is perceived.